Clinical Observation of Concomitant Congenital Heart Disease and Anomaly of the Urinary System in Adolescent - M.P. Limarenko; A.V. Golubitskaya; T.V. Smirnova (Zaslavsky O.Yu., 2014)
The article presents the clinical observation of multiple malformations in a child: combination of congenital heart disease with an anomaly of the urinary system on the background of undifferentiated connective tissue dysplasia syndrome of maximum severity. This case report is of interest to pediatricians. Children with defects of the heart and urinary system often have other malformations, so in these patients it is important to conduct a full multisystem examination.